Vaccine tourism: an emerging topic of discussion - Shah, Anuradha Kunal; Dakshit, Kosturi (International Journal Of Community Medicine And Public Health, 2021)
Vaccine tourism (also known as vaccine vacation) is a term that recently became popular once travel agents started offering tours abroad along with COVID-19vaccination doses as a package in early 2021. Vaccine tourism is a kind of medical tourism where people are offered to get two doses of COVID-19 vaccines, stay in that country, and a tour of that country. It is based on a 3- ‘V’ policy: Visit-Vaccination-Vacation. ‘Vaccine passport’ is a term often confused with vaccine tourism. A vaccine passport is a document of proof that the person has taken a vaccine against that particular disease and is asked to produce it at the point of entry to a different country. This is similar to an immunity passport in which a person is tested for an antibody after a certain duration of taking the vaccine and if the antibody is positive, that means the person is protected against that disease. The history of this goes back to the time when people entering the ‘British Pandharpur’ or pilgrims to Mecca for Hajj were asked for a vaccine certificate, a scar of vaccination, or pitted face as a sign of smallpox survival. For COVID-19 WHO has not advised in favor of vaccin